Mitigation policies, community mobility, and COVID-19 case counts in Australia, Japan, Hong Kong, and Singapore. (May 2021) - Hakim, A.J.; Victory, K.R.; Chevinsky, J.R.; Hast, M.A.; Weikum, D.; Kazazian, L.; Mirza, S.; Bhatkoti, R.; Schmitz, M.M.; Lynch, M.; Marston, B.J.
Abstract: Objectives: The objective of the study was to characterize the timing and trends of select mitigation policies, changes in community mobility, and coronavirus disease 2019 (COVID-19) epidemiology in Australia, Japan, Hong Kong, and Singapore. Study design: Prospective abstraction of publicly available mitigation policies obtained from media reports and government websites. Methods: Data analyzed include seven kinds of mitigation policies (mass gathering restrictions, international travel restrictions, passenger screening, traveler isolation/quarantine, school closures, business closures, and domestic movement restrictions) implemented between January 1 and April 26, 2020, changes in selected measures of community mobility assessed by Google Community Mobility Reports data, and COVID-19 epidemiology in Australia, Japan, Hong Kong, and Singapore. Results: During the study period, community mobility decreased in Australia, Japan, and Singapore; there was little change in Hong Kong. The largest declines in mobility were seen in places that enforced mitigation policies. Across settings, transit-associated mobility declined the most and workplace-associated mobility the least. Singapore experienced an increase in cases despite the presence of stay-at-home orders, as migrant workers living in dormitories faced challenges to safely quarantine. Conclusions: Public policies may have different impacts on mobility and transmission of severe acute respiratory coronavirus-2 transmission. When enacting mitigation policies, decision makers should consider the possible impact of enforcement measures, the influence on transmission of factors other than movement restrictions, and the differential impact of mitigation policies on subpopulations.